Mechanism of action of Yersinia enterocolitica enterotoxin. - Robins-Browne, R M (1979)
Enterotoxin derived from three clinical isolates of Yersinia enterocolitica was compared with the heat-stable enterotoxin of Escherichia coli. Both toxins were biologically active in infant mice examined at 2 h and in ligated rabbit ileal loops at 6 h. Neither substance, however, produced changes in ligated ileal loops at 18 h or in Chinese hamster ovary or Y1 adrenal tissue cultures. In addition, both Y. enterocolitica enterotoxin concentrated approximately 20 times by ammonium sulfate precipitation and ultrafiltration and a similarly prepared sample of E. coli heat-stable enterotoxin stimulated the activity of guanylate cyclase but not that of adenylate cyclase in infant mouse intestine. These findings suggest that the role of enterotoxin in the pathogenesis of intestinal Y.enterocolitica infection may be similar to that of heat-stable enterotoxin in E. coli diarrhea.